Gestión de la innovación de la Empresa Sociedad Unión Obrera y Progreso de la ciudad de Babahoyo, periodo 2023 - Defilippi León, Erick Giovanni (2024)
The Sociedad Unión Obrera y Progreso is an organization that offers Nursing and Pharmacology Assistant programs from Monday to Friday from 8:00 am to 5:30 pm. The company has been present in the medical industry for ten years, providing educational services. However, over time, their competitive advantage has faded due to a lack of innovation and vision, which led them to make mistakes and carry out activities without transformation. Thus, this study aims to evaluate the innovation management of the Sociedad Unión Obrera y Progreso in the city of Babahoyo for the period 2023. The methodology used deductive and inductive methods with an analysis process using strategic tools, as well as the correlation of variables that lead to threats and weaknesses that outweigh strengths. and opportunities. Therefore, although the situation seems good according to the weighting map, there is a high possibility that it will not be attractive to students who buy its services or even go bankrupt without new innovations and the inclusion of more study programs. Therefore, it is suggested to generate continuous improvement processes aimed at teachers so that they can provide better teaching methods and integrate new technologies which will allow them to attract more clients.